The inhibition of CHO-K1-BH4 cell proliferation and induction of chromosomal aberrations by brevetoxins in vitro - Sayer, A. N.; Hu, Q.; Bourdelais, Andrea J.; Baden, Daniel G.; Gibson, James E. (East Carolina University, 2006)
Brevetoxins (PbTxs) are highly potent trans-syn polyether neurotoxins produced during blooms of several species of marine dinoflagellates, most notably Karenia brevis. These neurotoxins act on voltage-sensitive sodium channels prolonging the active state. During red tides, the commercial fishing and tourism industries experience millions of dollars of lost revenue. Human consumption of shellfish contaminated with PbTxs results in neurotoxic shellfish poisoning (NSP). Additionally, blooms of K. brevis are potentially responsible for adverse human health effects such as respiratory irritation and airway constriction in coastal residents. There is little information regarding the full range of potential toxic effects caused by PbTxs. Recent evidence suggests that PbTxs are genotoxic substances. The purpose of this study was to determine if PbTxs could induce chromosomal aberrations and inhibit cellular proliferation in CHO-K1-BH4 cells, and if so, could the damage be negated or reduced by the PbTx antagonist brevenal. Results from the chromosomal aberrations assay demonstrated that PbTxs are potent inducers of CHO-K1-BH4 chromosome damage. Results from the inhibition of cellular proliferation assays demonstrated that PbTxs inhibit the ability of CHOK1- BH4 cells to proliferate, an effect which can be reduced with brevenal. Originally published Food and Chemical Toxicology, Vol. 44, No. 7, July 2006
Keywords: Brevetoxin; Brevenal; Cell proliferation; Chromosomal aberration; Neurotoxic shellfish poisoning; Genotoxic